2023
DOI: 10.3389/fmed.2023.1163565
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-infiltrating lymphocytes and tumor-associated macrophages as potential predictors of lymph node metastases in major salivary gland cancers

Abstract: PurposeThe purpose of this study is to define if tumor-infiltrating lymphocytes (TILs) and tumor-associated macrophages (TAMs) could represent potential predictors of lymph node metastases (LNM) in salivary gland cancers (SGC).MethodsA selected number of immunohistochemical markers related to TILs (CD3, CD4, CD68, and FOXP3) and TAMs (CD68 and CD163) were investigated on major salivary gland cancers. TIL and TAM densities were measured on digital images using the open-source QuPath both in the tumor interior (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
3
4
0
Order By: Relevance
“…In addition, the low expression of CD3 in the intra-tumoral area of malignant SGTs showed a significant association with those still alive patients. In line with our findings, another investigation revealed that the only low-grade MEC with no recurrences during the follow-up showed low CD3 positivity [20]. Elevated CD3 expression may not necessarily reflect T cell functionality.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In addition, the low expression of CD3 in the intra-tumoral area of malignant SGTs showed a significant association with those still alive patients. In line with our findings, another investigation revealed that the only low-grade MEC with no recurrences during the follow-up showed low CD3 positivity [20]. Elevated CD3 expression may not necessarily reflect T cell functionality.…”
Section: Discussionsupporting
confidence: 90%
“…AdCCs demonstrated low CD3 and scant CD20 expression in the intra-tumoural areas and lower TIL counts compared to those for MECs and PAs in peripheral areas. This tumor is considered to be low in immunogenic levels (poor immunogenicity) [16,20]. In line with our data, some authors have observed that most AdCC cases present with few infiltrating immune cells, including T lymphocytes [18].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations